REPOSITIONING BUSINESS EDUCATION TO ADDRESS EDUCATIONAL INEQUALITY IN NIGERIA'S RECESSED ECONOMY (NAU Journal of Technology and Vocational Education, 2026)
Nigeria’s recessed economy, marked by inflation, declining Gross Domestic Product (GDP), and high unemployment, has exacerbated educational inequality, particularly in access to Business Education. This study explored how Business Education can be repositioned to reduce inequality and promote inclusive economic participation. The problem lies in certain barriers: underfunding, urban-rural divides, and gender biases which limit access to Business Education for marginalized groups. The aim of the study is to propose strategies for making Business Education more inclusive and impactful in a challenged economic context. The study adopted a desktop research approach, drawing on relevant literature, policy documents, and institutional reports, which were analyzed thematically. Findings reveal that Business Education holds great potential for fostering entrepreneurship, enhancing employability, and equipping individuals with practical skills for economic recovery. However, inequalities in access and curriculum relevance hinder its full impact. The study concludes that repositioning Business Education for equity is both a developmental necessity and a national economic strategy. Recommendations include policy reform, curriculum overhaul, community-based education centers, and gender-inclusive programming to drive access and economic resilience.
Keywords: Business Education; Educational; Human Capital; Inequality; Nigeria; Recessed Economy